2001
DOI: 10.1046/j.1468-3083.2001.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic radiation ulcers with recombinant platelet‐derived growth factor and a hydrophilic copolymer membrane

Abstract: We report on a 59-year-old woman suffering from cutaneous T-cell lymphoma of the mycosis fungoides type, who developed chronic ulcerating radiation dermatitis after total body electron beam irradiation with a cumulative dose of 36 Gy. The painful and easily bleeding ulcers could be markedly improved using a combined approach with topical platelet-derived growth factor gel and hydrophilic copolymer membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…9,136,145 Recombinant PDGF and hydrophilic copolymer membranes have also been utilized to treat chronic radiation-induced ulcers. 134 Topical or oral antibacterial agents should be considered in the treatment of wounds that are at high risk or are already infected. Silver-based dressings are antibacterial and have proven to be effective for this purpose.…”
Section: Wound Care For Erosions and Ulcersmentioning
confidence: 99%
See 1 more Smart Citation
“…9,136,145 Recombinant PDGF and hydrophilic copolymer membranes have also been utilized to treat chronic radiation-induced ulcers. 134 Topical or oral antibacterial agents should be considered in the treatment of wounds that are at high risk or are already infected. Silver-based dressings are antibacterial and have proven to be effective for this purpose.…”
Section: Wound Care For Erosions and Ulcersmentioning
confidence: 99%
“…147 Chronic radiation ulcers after electron beam therapy were treated successfully with PDGF gel and hydrophilic copolymer membrane. 134 If there is active tumor, there may be some theoretical risk in the use of growth factors, and some topical dressings may partially absorb or inactivate this expensive product.…”
Section: Targeted Biologic Therapymentioning
confidence: 99%
“…Wollina et al also reported a case of a patient who developed chronic URS on her trunk after total body electron beam irradiation. The combination of PDGF gel and hydrophilic copolymer membranes markedly improved healing potency (granulation and reepithelialisation) and pain relief (69).…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…7 Bu yara örtüsü ayrıca, dermabrazyon yapılan hastaların cerrahi sonrası bakımında, serbest fleplerde kapiller dolumun izlenmesine izin veren bir kapatıcı örtü olarak, deri greftlerinde, CO 2 lazer ile deri yenileme işlemi sonrasında ve trombosit kö-kenli büyüme faktörüyle birlikte kronik radyasyon ülserlerinde kullanılmıştır. [8][9][10][11][12] Omiderm üzerine antibakteriyel ilaçların kullanılabilmesi ve örtünün bakterilere geçirgen olmaması nedeni ile yara enfeksiyonu riski çok azdır. Bununla birlikte, bir bebekte bu yara örtüsünün yanık yarası üzerine uygulanması sonrasında toksik şok sendromu geliştiği bildirilmiştir.…”
Section: 2unclassified